Chudley-McCullough Syndrome: Case Report and Review of the Neuroimaging Spectrum - Kau, Thomas; Veraguth, Dorothe; Schiegl, Heinrich; Scheer, Ianina; Boltshauser, Eugen (Neuropediatrics, 2012)
We report on a child with Chudley-McCullough syndrome and re-evaluate the spectrum of imaging findings (in 15 previously reported patients) which appear to be variable and, to some extent, ambiguous in the literature. Magnetic resonance imaging of the brain revealed asymmetric colpocephaly with agenesis of the splenium corporis callosi, ribbon-like subcortical gray matter heterotopia along the cingulate gyri, malrotation of both hippocampi, and dysplasia of the cerebellum. Macrocrania together with sensorineural hearing loss, colpocephaly, and posterior or complete agenesis of the corpus callosum can be considered the hallmarks of the autosomal recessive Chudley-McCullough syndrome. These may be variably associated with interhemispheric arachnoid cyst, cortical dysplasia, gray matter heterotopia, and cerebellar dysplasia. While early support with hearing aids may lead to improved language and cognitive outcome, shunting of ventricular dilatation is not indicated in the Chudley-McCullough syndrome.
Keywords: sensorineural hearing loss; corpus callosum dysgenesis; colpocephaly; gray matter heterotopia; cerebellar dysplasia